An Analysis of Medical Waste Management Practices During and After Covid-19: A Case of B&C Hospital, Nepal - Dhakal, Anuradha; Pokharel, Gobinda Prasad (Journal of Physical and Life Sciences, 2024)
During COVID-19, Nepal witnessed an increase in the generation of highly infectious waste, including contaminated needles, syringes, soiled bandages, and disposable personal protective equipment. The study aims to assess the waste management practices at B&C Hospital and evaluate the awareness level of various hospital personnel through a questionnaire involving 105 and 200 respondents during and after COVID-19 in B&C Hospital, Jhapa, Nepal. This Study shows that hospital practiced source segregation and disinfection using chemicals and autoclaves, both during and after COVID-19. While 100% of doctors and administrative staff were aware of waste management, the awareness levels among visitors were comparatively lower, 52% during COVID-19 and 80% after the pandemic. Regarding the practice of color-coded waste segregation, 85% and 100% of respondents confirmed its implementation during and after COVID-19. The study was conducted over two periods: March 13 to July 14, 2021, and July 1 to December 31, 2024. The maximum degradable waste generation during COVID-19 was recorded in March at approximately 3.17 kg/day whereas after COVID-19 the highest degradable waste was observed in October reaching 11.6 kg/day. The hospital’s total waste generation during COVID-19 was estimated at 151.9 kg/day, comprising 65% non-hazardous and 35% hazardous waste. Post-COVID-19, the total waste generation increased to 483.5 kg/day with 72% classified as non-hazardous and 28% as hazardous. Based on these findings, it is recommended that B&C Hospital strengthen its regulatory measures for waste management and explore the implementation of appropriate waste-to-bioenergy technologies to enhance sustainability and environmental safety.